Structural Evolution of Multilayer SnS/Cu/ZnS Stack to Phase-Pure Cu2ZnSnS4 Thin Films by Thermal Processing. (27th January 2015) - Avendaño, C. A. Meza; Mathews, N. R; Pal, Mou; Delgado, F. Paraguay; Mathew, X.
Abstract : In this work, thin films of phase-pure Cu2 ZnSnS4 (CZTS) were developed from a stack of binary metal sulfides by post-deposition thermal processing. The precursor stack SnS/Cu/ZnS was grown by sequential electrodeposition of SnS and Cu layers followed by thermal evaporation of ZnS layer. The transformation from binary/ternary composition to phase-pure CZTS was studied using different experimental tools such as X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). The TEM images revealed the formation of tetragonal crystals with interplanar spacing 0.312 nm. Raman spectra of the films confirmed that annealing at 550°C for 30 min under N2 /S ambient resulted in the formation of phase-pure CZTS film. The bandgap estimated from the optical transmittance and reflectance spectra showed a direct transition at 1.59 eV. The films are photosensitive and the photo electrochemical measurements showed the p-type conductivity of the films.